Assistance for business startups processing Etawa goat's milk to maximize local potential in Purworejo - Titin Ekowati; Fithri Rahmawati; Esti Margiyanti Utami (Community Empowerment, 2022)
This community service program is carried out to help startup business actors. Beginner business actors are expected to be able to develop businesses that have been initiated with their groups. The purpose of this community service program is to offer business support to start-up business groups that produce "Scrub Etta" from goat's milk from Etawa goats. How to handle this program requires assistance in the production process, assistance in product marketing, assistance in the preparation of business financial reports, and assistance in developing business networks. As a result, the pilot group was able to develop sound business plans, successfully implement business strategies with profitable results, develop various advertising and promotion tools, and enforce acting relationships with suppliers and customers. In addition, the program also supports business startup groups to gain knowledge on everything from corporate practices to business plan preparation.